Contribution of Post-translational Phosphorylation to Sarcomere-Linked Cardiomyopathy Phenotypes - Westfall, Margaret V. (Frontiers in Physiology, 2016)
Secondary shifts develop in post-translational phosphorylation of sarcomeric proteins in multi¬ple animal models of inherited cardiomyopathy. These signaling alterations together with the primary mutation are predicted to contribute to the overall cardiac phenotype. As a result, identification and integration of post-translational myofilament signaling responses are identified as priorities for gaining insights into sarcomeric cardiomyopathies. However, significant questions remain about the nature and contribution of post-translational phosphorylation to structural remodeling and cardiac dysfunction in animal models and human patients. This perspective essay discusses specific goals for filling critical gaps about post-translational signaling in response to these inherited mutations, especially within sarcomeric proteins. The discussion focuses primarily on pre-clinical analysis of animal models and defines challenges and future directions in this field.